2022
DOI: 10.3390/su142113706
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Temporal and Spatial Distribution Characteristic of Traffic Accidents in China

Abstract: The interaction among social economy, geography, and environment leads to the occurrence of traffic accidents, which shows the relationship between time and space. Therefore, it is necessary to study the temporal and spatial correlation and provide a theoretical basis for formulating traffic accident safety management policies. This paper aims to explore the traffic accident patterns in 31 provinces of China by using statistical analysis and spatial clustering analysis. The results show that there is a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There is currently no widely accepted concept for identifying Road Traffic Crash (RTC) hot spots [ 7 ]. The spatial statistics method has recently been used to understand the characteristics of the spatial and temporal distribution of road traffic crashes [ [17] , [18] , [19] , [20] ]. In order to identify hotspots with regard to time and compare the hotspots in terms of crash type and severity index, the crash pattern was analyzed at the TAZ level in Iran using the spatial autocorrelation method [ 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is currently no widely accepted concept for identifying Road Traffic Crash (RTC) hot spots [ 7 ]. The spatial statistics method has recently been used to understand the characteristics of the spatial and temporal distribution of road traffic crashes [ [17] , [18] , [19] , [20] ]. In order to identify hotspots with regard to time and compare the hotspots in terms of crash type and severity index, the crash pattern was analyzed at the TAZ level in Iran using the spatial autocorrelation method [ 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma et al [6] used density analysis to identify high accident areas based on the road traffic accident data in Wales in 2017, and outlier and hotspot analysis models to identify areas with high accident severity and determine the clustering characteristics of accidents. Yang et al [7] used 2002-2019 based on traffic accident data from 31 provinces in China and studied the spatial autocorrelation characteristics and spatial heterogeneity between provinces and regions using statistical analysis and spatial autocorrelation analysis.…”
Section: Study On Road Accident Characteristicsmentioning
confidence: 99%
“…Research has shown that there is a significant spatial autocorrelation between traffic accidents in various provinces and cities in China, which means that the number of traffic accidents and deaths is high with high aggregation, which leads to traffic congestion in populated areas, resulting in the waste of resources and inability to reflect sustainable development. Traffic accidents will not only threaten people's safety; improper emergency response will increase rescue time, cause secondary damage to the accident site, waste resources, and hinder sustainable development [3]. In the actual emergency disposal process of highway emergencies, the accident site is often complex, the response time of the emergency department is urgent, and there is a lack of adequate communication between multiple emergency departments, which makes the emergency departments unable to fully understand the progress of the accident site, resulting in poor cooperation between the emergency departments and low emergency rescue efficiency.…”
Section: Introductionmentioning
confidence: 99%